2020
DOI: 10.1136/bmjresp-2020-000639
|View full text |Cite
|
Sign up to set email alerts
|

Is continuous positive airway pressure (CPAP) a new standard of care for type 1 respiratory failure in COVID-19 patients? A retrospective observational study of a dedicated COVID-19 CPAP service

Abstract: The aim of this case series is to describe and evaluate our experience of continuous positive airway pressure (CPAP) to treat type 1 respiratory failure in patients with COVID-19. CPAP was delivered in negative pressure rooms in the newly repurposed infectious disease unit. We report a cohort of 24 patients with type 1 respiratory failure and COVID-19 admitted to the Royal Liverpool Hospital between 1 April and 30 April 2020. Overall, our results were positive; we were able to safely administer CPAP ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
4
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 2 publications
8
56
4
3
Order By: Relevance
“…intubation rate of 38%, which was similar to our results [27]. A French two period retrospective study favours CPAP over oxygen: intubation-free survival was 77% (29/38) with CPAP compared to 43% (6/14) with oxygen (p = 0,043).…”
Section: Plos Onesupporting
confidence: 90%
“…intubation rate of 38%, which was similar to our results [27]. A French two period retrospective study favours CPAP over oxygen: intubation-free survival was 77% (29/38) with CPAP compared to 43% (6/14) with oxygen (p = 0,043).…”
Section: Plos Onesupporting
confidence: 90%
“…Encouragingly, within the UK (April 2020) a positive case series review of 24 patients who received CPAP treatment, demonstrated that 58% of patients avoided mechanical ventilation and that there was a remarkable 79% survival rate. 18 Additionally, beneficial CPAP impact on prognosis has been demonstrated where non-responders had a double increase in mortality when compared with responders. 19 On reflection and as evidence emerges, our experiences in developing care pathways in the treatment of COVID-19 have potentially been mirrored throughout the UK and internationally.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is concordant to other case series even if still few data on NIPPV failure in these patients are available. 18 Patients who were intubated had a signi cant lower P/F ratio compared to those treated only with NIPPV.…”
Section: Discussionmentioning
confidence: 90%
“…38 patients (73%) were judged eligible for ETI. 18 (34.6%) were intubated. 16 (30.8%) patients died: 7 (38.9%) and 9 (26.5%) in the ETI and non-ETI group respectively.…”
Section: Resultsmentioning
confidence: 99%